Hubungan Kepatuhan Minum Obat dan Status Gizi dengan Kesembuhan Pasien Tuberkulosis Paru di Kecamatan Katobu Kabupaten Muna - Muhajir Muhajir; Adius Kusnan; Arimaswati Arimaswati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
TuberculosisisainfetiondiseasecausedbyMycobacteriumtuberculosis. This disease can attack intra-lung and extra-lung. It spreads through the air and droplets such as coughing, sneezing, and direct contact with the sputum of patients with pulmonary tuberculosis. The healing of tuberculosis patients is influenced by factors including adherence to taking medication, nutritional status, job, and supervisor of taking medicine. The purpose of this study to determine the relationship between medication compliance and nutritional status in the recovery of pulmonary tuberculosis patients in Katobu District Muna Regency. The design of this study is an observational study with a cross-sectional approach. The number of samples used in this study was 61 samples according to the inclusion and exclusion criteria selected by the simple proportional stratified random sampling method. The data is processed using Univariate and Bivariateanalysiswith the Chi-Squarestatisticaltest. The results of this study indicate that the variable medication compliance with pvalue=0.002 and r=0,366, the nutritional status variable with pvalue=0.000 and a value of r=0,539, has a relationship in the recovery of pulmonary tuberculosis patients. The conclusion of this study is that medication compliance and nutritional status is associated with the recovery of pulmonary TB patients in Katobu District Muna Regency